Effect of Ba doping on electrochemical performance of Li3V2(PO4)3/C cathode materials for Li ion batteries. (25th January 2018) - Xin-wei, Wang; De-xuan, Pei; Ting, Xue; Fang-hong, Li; Zong-hong, Ma
ABSTRACT: Ba-doped Li3 V2-x Bax (PO4 )3 /C (x = 0.00, 0.10, 0.15, 0.20) composite was synthesized by Sol-gel Method. The effects of Ba doping on the structure, morphology and electrochemical performance of Li3 V2 (PO4 )3 /C were investigated by X-ray diffraction (XRD), scanning electron microscopy (SEM), Transmission electron microscopy (TEM) and electrochemical measurements. The XRD analysis showed that these Ba-doped materials did not change the crystal structure of Li3 V2 (PO4 )3 /C cathode material. In the potential range of 3.0–4.3 V, the Li3 V2-x Bax (PO4 )3 /C (x = 0.00, 0.10, 0.15, 0.20) composite showed the highest discharge capacity of 125.6 mAh/g at 0.1 C, which is close to the theoretical capacity. The discharge capacity of the sample was stable even after 40 th cycles.